Strategies for Transforming Applied Competency Based Curriculum to Address Graduate Unemployment at State Islamic Religious Universities - Burhanudin Hartono (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
The high rate of open unemployment among university graduates, particularly within State Islamic Religious Universities, represents a crucial challenge for human capital development in Indonesia for the 2021–2025 period. This phenomenon is driven by a significant competency gap between academic curricula, which are dominated by theoretical content, and the actual needs of the business and industrial sectors. This policy paper aims to formulate strategies for addressing unemployment through the transformation of a more responsive and applied curriculum. The analysis is conducted by applying a comprehensive policy evaluation framework, beginning with problem identification using the Urgency, Seriousness, and Growth method to objectively map issue priorities. Subsequently, an assessment of various policy intervention alternatives is performed using William N. Dunn’s six evaluation criteria, which include effectiveness, efficiency, adequacy, equity, responsiveness, and technical feasibility. The results of the analysis indicate that the absence of regulations requiring curriculum partnerships with industry is a primary obstacle in synchronizing graduate competencies. As a strategic solution, this paper recommends the issuance of a Decree of the Minister of Religious Affairs concerning Guidelines for the Development of Applied Competency-Based Curricula. This policy mandates the restructuring of credit loads with a significant portion dedicated to practical work and the integration of digital literacy as a minimum standard for learning outcomes. Through this approach, it is expected that a strong link-and-match synergy will be established between educational institutions and the labor market, thereby sustainably reducing the rate of educated unemployment. The implementation of this policy is an urgent step to ensure that university graduates possess not only a textual religious understanding but also competitive functional agility on both national and international scales.